RESEARCH ON THE OPTIMAL ACCELERATION LIMIT METHOD FOR COMPILING LOAD SPECTRUM OF VEHICLE ROAD SIMULATION TEST - ZHU LianFeng; YU JiaWei; ZHENG SongLin; LI YuXiao; JIN Qing; LIU Xin (Jixie qiangdu)
Road simulation test has become an important means to develop the vehicle with high quality and high efficiency, but there is no uniform criterion for compiling the load spectrum of road simulation test. In this paper, the time-domain damage editing method was applied to compile the measured load spectra from a vehicle proving ground. By studying the change tendencies of time shortening rate, damage attenuation rate and load characteristics（time,amplitude and frequency domain） of the developed accelerated spectra, An optimal accelerated spectrum compilation limiting principle was proposed based on load characteristic changes and relative change rate（relative change rate=damage attenuation rate/time shortening rate）. The flow chart of compiling test load spectrum according to the optimal accelerated spectrum compilation limit criterion was put forward, and the flow chart of compiling test load spectrum under each typical working condition was applied in the test field. Finally, a vehicle road simulation test was established by using the accelerated spectrum, which achieves a good simulation effect of load spectrum and verifies the rationality of the method.